2020
DOI: 10.3991/ijet.v15i02.11602
|View full text |Cite
|
Sign up to set email alerts
|

Using a Personalized Learning Style and Google Classroom Technology to Bridge the Knowledge Gap on Computer Science

Abstract: The article is devoted to the challenge of bridging the knowledge gap on computer science in context of the Kazakhstani education. The authors discuss the main reasons of gap in knowledge on computer science at first-year students and suggest suitable teaching to solve the indicated challenge. The considered teaching is based on the principle of continuity to teaching which provide correlation between various levels of education and improving the effectiveness of teaching. The different levels of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 11 publications
(12 reference statements)
1
6
0
Order By: Relevance
“…The possibility to perform an interactive task repeatedly provides consolidation of knowledge and developing hands-on skills on topics such as designing of an architecture, using components, defining outlets, class properties, coding, thereby developing necessary cognitive skills. In addition, the DER can be implemented both in LMS and interactive platforms, for example, Google Classroom, for implementing personalized learning technology [41], [42].…”
Section: Resultsmentioning
confidence: 99%
“…The possibility to perform an interactive task repeatedly provides consolidation of knowledge and developing hands-on skills on topics such as designing of an architecture, using components, defining outlets, class properties, coding, thereby developing necessary cognitive skills. In addition, the DER can be implemented both in LMS and interactive platforms, for example, Google Classroom, for implementing personalized learning technology [41], [42].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies (e.g. Amro et al, 2013;Ansong-Gyimah, 2020;Back et al, 2016;Dash, 2019;Kopeyev et al, 2020;Ventayen et al, 2018) found the efficacy of LMS and GC in non-ELT instruction. For example, Dash (2019) found that medical-school students with limited learning resources in India have greater learning access, facilitating learning efficiency and promoting better interaction patterns (Back et al (2016).…”
Section: Introductionmentioning
confidence: 92%
“…In conditions of profile training it assumes saturation of the content of a school mathematics course with its applications arising in various spheres of human activity, taking into account specificity of developed profile directions, and also interests, aptitudes and possibilities of pupils that allows to solve problems of individualization of educational process to a fuller extent [23].…”
Section: Structure and Content Of The Course "Fundamentals Of Financialmentioning
confidence: 99%